PERUBAHAN BENTUK DAN UKURAN BENIH DUA KULTIVAR KEDELAI (Glycine max (L.) Merr.) DI JATINANGOR DAN CIKAJANG - Siti Rodiah; Zulfatunnisa Zulfatunnisa; Sumadi Sumadi; Anne Nuraini; Meddy Rachmadi; Noladhi Wicaksana; Muhammad Kadapi (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2017)
The variation of the seed size in each species and individuals might be from of difference species adaptation for a difference environment. This difference may also arise from the constraints of limited formation of seed size. The use of adaptive ciltivars on the growth environment is very influential on the succes in the farm field. This research was aimed to find the adaptation of phase and size seed of two cultivars of soybeans in Jatinangor and Cikajang. This research was held in Jatinangor (Sumedang regency) and Cikajang (Garut regency) from April to July 2016. The design that used in this research was Randomized Block Design (RBD) and Duncan at 5% rate. Improved cultivars that tested in this research were placed at Grobogan and Anjasmoro which were repeated 5 times. The results of experiment showed that adaptation of size seed showed of 100 grains and large seeds. The low temperature condition can increase of variability of seed size. Heterogeneity of environment can not sustain the size of soybean seed. Genetic and environment factors influence significantly for weight of 100 grains and seed size Grobogan in Jatinangor. The weight of 100 grains Grobogan in Jatinangor and Cikajang haved a greater than Anjasmoro. Environmental factors influence yield of soybean, weight of 100 grains of cultivars in Cikajang haved a greater than Jatinangor caused by the seed size.